ESTIMATING THE INTENSITY OF GERM-GRAIN MODELS WITH OVERLAPPING GRAINS - Ghorbani, Hamid; Stoyan, Dietrich (Image Analysis and Stereology, 2011)
Formulas are derived for the spherical contact distribution of a planar germ-grain model Z with circular grains where the germs formeither a 'segment cluster' process or a 'line-based' Poisson point process. They are used in order to estimate the intensityl of the germprocess by means of the spherical contact distribution function. As an application the number of dislocations on a silicon wafer is estimated.